2018
DOI: 10.1038/s41598-018-20790-7
|View full text |Cite
|
Sign up to set email alerts
|

Female dispersion and sex ratios interact in the evolution of mating behavior: a computational model

Abstract: The evolution of mating strategies is not well understood. Several hypotheses have been proposed to explain the variation in mating strategies, with varying levels of support. Specifically, female dispersion, adult sex ratio and mate guarding have been proposed as drivers of the evolution of monogamous strategies. In this study, we used an agent-based model (ABM) to examine how different mating behaviors evolve in a population under different conditions related to these putative drivers, looking to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…One of the world's smallest seahorse species, the dwarf seahorse Hippocampus zosterae Jordan & Gilbert 1882, also exhibits extreme degrees of parental care and has been shown to exhibit social monogamy within a brood (Masonjones & Lewis, ) and were confirmed to engage in genetic monogamy within broods in wild populations (Rose et al, ). In monogamous species, expected sex ratios are even to male‐biased (Gomes et al, ), with deviations from even sex ratios leading to mate switching and other non‐monogamous behaviour (Liker et al, ). A review of the literature found Hippocampus spp.…”
Section: Introductionmentioning
confidence: 99%
“…One of the world's smallest seahorse species, the dwarf seahorse Hippocampus zosterae Jordan & Gilbert 1882, also exhibits extreme degrees of parental care and has been shown to exhibit social monogamy within a brood (Masonjones & Lewis, ) and were confirmed to engage in genetic monogamy within broods in wild populations (Rose et al, ). In monogamous species, expected sex ratios are even to male‐biased (Gomes et al, ), with deviations from even sex ratios leading to mate switching and other non‐monogamous behaviour (Liker et al, ). A review of the literature found Hippocampus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical models often relied on assumptions that exaggerate the efficiency of male control, e.g. as long as a male attempts to guard his female, she has no opportunity to cheat [19,[54][55][56][57]. Empirical studies demonstrated, however, mate guarding can often be inefficient due to various reasons, including: (1) female birds and mammals can often escape male paternity guarding, such as in the bluethroats (Luscinia svecica) [58], the yellow-breasted chats (Icteria virens) [59], the superb fairy-wrens (Malurus cyaneus) [60] and the Sika deer (Cervus nippon) [61]; (2) paired males may face a tradeoff between guarding and parental care, such as in black coucals (Centropus grillii), where parental care is provided by the males only, and once males start to incubate a (still incomplete) brood, they cannot prevent female EPC as efficiently as before, and consequently, EPO occur more often in the later-laid eggs [62]; and (3) females may use stored sperm of previous mates, which is often found in insects including burying beetles [17], golden egg bugs (Phyllomorpha laciniata) [63], and a bee species (Ceratina nigrolabiata) [64].…”
Section: Discussionmentioning
confidence: 99%
“…Prevailing models explaining mating system diversity emphasize links between resource and mate monopolization. If resources are defensible, polygynous males on high-quality territories will have access to more females than monogamous males on lowquality territories (Verner and Willson 1966;Orians 1969), and temporal variation in mate availability or sex ratio further accentuates this dichotomy between polygyny and monogamy (Emlen and Oring 1977;Houston et al 2013;Gomes et al 2018). However, paternal care can shift the advantage to a monogamous system (Maynard Smith 1977;Wakano and Ihara 2005;Jungwirth and Johnstone 2018).…”
Section: Introductionmentioning
confidence: 99%